Growth hormone in the dwarf dopaminergic D2R knockout mouse: somatotrope population, GH release and responsiveness to GH-releasing factors and somatostatin - Garcia Tornadu, Isabel Andrea (2006)
Recently, the importance of the dopaminergic D2 receptor (D2R) subtype in normal body growth and neonatal GH secretion has been highlighted. Disruption of D2R alters the GHRH-GH-IGF-I axis and impairs body growth in adult male mice. The D2R knockout (KO) dwarf mouse has not been well characterized; we therefore sought to determine somatotrope function in the adult pituitary. Using immunohistochemistry and confocal microscopy, we found a significant decrease in the somatotrope population in pituitaries from KO mice (P=0.043), which was paralleled by a decreased GH output from pituitary cells cultured in vitro. In cells from adult mice the response amplitude to GHRH differed between genotypes (lower in KO), but this difference was less dramatic after taking into account the lower basal release and hormone content in the KO cells. Furthermore, there were no significant differences in cAMP generation in response to GHRH between genotypes. By Western blot, GHRH-receptor in pituitary membranes from KO mice was reduced to 46% of the level found in wildtype (WT) mice (P=0.016). Somatostatin induced a concentration-dependent decrease in GH and prolactin (PRL) secretion in both genotypes, and 1x10(-7) M ghrelin released GH in cells from both genotypes (P=0.017) in a proportionate manner to basal levels. These results suggest that KO somatotropes maintain a regulated secretory function. Finally, we tested the direct effect of dopamine on GH and PRL secretion in cells from both genotypes at 20 days and 6 months of life. As expected, we found that dopamine could reduce PRL levels at both ages in WT mice but not in KO mice, but there was no consistent effect of the neurotransmitter on GH release in either genotype at the ages studied. The present study demonstrates that in the adult male D2R KO mouse, there is a reduction in pituitary GH content and secretory activity. Our results point to an involvement of D2R signaling at the hypothalamic level as dopamine did not release GH acting at the pituitary level either in 1-month-old or adult mice. The similarity of the pituitary defect in the D2R KO mouse to that of GHRH-deficient models suggests a probable mechanism. A loss of dopamine signaling via hypothalamic D2Rs at a critical age causes the reduced release of GHRH from hypophyseotropic neurons leading to inadequate clonal expansion of the somatotrope population. Our data also reveal that somatotrope cell number is much more sensitive to changes in neonatal GHRH input than their capacity to develop properly regulated GH-secretory function.